2012
DOI: 10.1007/s13353-012-0115-z
|View full text |Cite
|
Sign up to set email alerts
|

A new case with 10q23 interstitial deletion encompassing both PTEN and BMPR1A narrows the genetic region deleted in juvenile polyposis syndrome

Abstract: We report on a patient with a contiguous interstitial germline deletion of chromosome 10q23, encompassing BMPR1A and PTEN, with clinical manifestations of juvenile polyposis and minor symptoms of Cowden syndrome (CS) and Bannayan-Riley-Ruvalcaba syndrome (BRRS). The patient presented dysmorphic features as well as developmental delay at the age of 5 months. Multiple polyps along all parts of the colon were diagnosed at the age of 3 years, following an episode of a severe abdominal pain and intestinal bleeding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Moreover, 10qdel syndrome is accompanied by macrocephaly with symptoms of autism and epilepsy ( 58 60 ). The genes encoding PTEN and bone morphogenetic protein receptor type 1A in this genomic region have been suggested as the culprits, but the molecular basis of 10qdel syndrome has not been clearly elucidated ( 61 , 62 ). Given that Gcap14 deficiency causes neurodevelopmental defects with thickening of the cortex reminiscent of macrocephaly seen in 10qdel syndromes, it is intriguing to speculate the contribution of Gcap14 deficiency to the 10qdel syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 10qdel syndrome is accompanied by macrocephaly with symptoms of autism and epilepsy ( 58 60 ). The genes encoding PTEN and bone morphogenetic protein receptor type 1A in this genomic region have been suggested as the culprits, but the molecular basis of 10qdel syndrome has not been clearly elucidated ( 61 , 62 ). Given that Gcap14 deficiency causes neurodevelopmental defects with thickening of the cortex reminiscent of macrocephaly seen in 10qdel syndromes, it is intriguing to speculate the contribution of Gcap14 deficiency to the 10qdel syndromes.…”
Section: Discussionmentioning
confidence: 99%
“… a Our case; b Lachlan et al (2007) ; c Tsuchiya et al (1998) ; d Gorensek et al (1984) ; e Hiljadnikova Bajro et al (2013) ; DD, developmental delay; M, male; PHTS, PTEN hamartoma tumor syndrome. …”
Section: Discussionmentioning
confidence: 99%
“…This leads to the loss of both PTEN and BMPR1A 28 ; a situation that can also look like BRRS, also known as juvenile polyposis of infancy (see section on JPS). 110,111 In a smaller study of 19 patients with CS (in which only 12 were shown to have germline pathogenic variants in PTEN), pancolonic polyps were found in 58%, pan-gastrointestinal polyps in 42%, and the pathological interpretation of the polyps included inflammatory polyps in 95%, but also adenomas, lipomas, and ganglioneuromas. 112 Moreover, there was more than 1 pathological variety in 79% of patients, indicating the clinical heterogeneity in this entity.…”
Section: Gastrointestinal Polyps and Polyposismentioning
confidence: 99%
“…This leads to the loss of both PTEN and BMPR1A 28 ; a situation that can also look like BRRS, also known as juvenile polyposis of infancy (see section on JPS). 110,111…”
Section: Pten-hamartoma Tumor Syndromementioning
confidence: 99%